Mapeamento da alteração de corbetura vegetal no Distrito Agropecuário da Suframa (DAS) utilizando séries temporais de sensores remotos - (:unkn) unknown (Universidade Federal do Amazonas, 2007)
The present study had as objective to map the forest land cover of the Farming District of SUFRAMA, from the interpretation of time series of products of remote sensors, using of scenes of sensor TM satellite LANDSAT 5 (2002 and 2004) and scenes of sensor CCD of satellite CBERS 2 (2006). The total area of the Farming District of SUFRAMA is 589.334 hectares and located at 2º 43 46 - 2º 04 21 South and 60º 40 - 59º 20 West, in the Manaus and Rio Preto da Eva City, Amazonas State. The occupation of lands stimulates the substitution of the original forest cover and follows a pattern associated with the existing ways of circulation, the presence of the federal highway BR-174 (in the direction North and South) and a state highway AM-010. The main cultives observed are: dendê, banana, coconut, orange, manihot, vegetables and grassy cultive. The great amount of abandoned projects is notable, for the lack of incentives or assistance agricultural technique and difficulty of sale the production in the rain periods. It is common also to observe areas of pasture degraded, depending on the time of abandonment, presented of capoeira in some stages of development. Considering the inherent difficulties the territorial management of the District, the present study developed a method to calculate the values of the legal reserve. Its calculated deforestation taxes as criterion of evaluation of the approval of new projects and/or the continuity of the effective ones by SUFRAMA. Considering the values observed in the period between 2002 and 2004, the deforestation grew 19.6%. The analysis of the 2006 image did not present significant alterations in the vegetal covering, only in the south portion, in the area of influence of Rio Preto da Eva City. 11,6% of modified areas observed in 2004 do not reach the boundary-values of 20% of the legal reserve of the Farming District. The possibility of it deforests more 8.4% of the total area, the limit for the withdrawal of the forest is fixed in the maximum value of 49.504,06 hectares. This work brings recommendations to the process of construction of the scientific knowledge in the Amazônia, mainly, in that it refers to the commitment of the sustainable development of the existing productive systems, having for base the diverse tools of the geotechnologies.
Keywords: SUFRAMA; Mapeamento com sensores remotos; Sistema de Informações Geográficas; Distrito Agropecuário da Suframa (DAS); CIÊNCIAS AGRÁRIAS